Penerapan Pelapis Dinding Kawat Ayam di Desa Koto Marapak Kabupaten Padang Pariaman - Monika Natalia; Zulfira Mirani; Yan Partawijaya (Universitas Lancang Kuning, 2021)
Earthquake-safe house, the costs not expensive. We can eliminate earthquake damage by strengthening our house while paying attention the rules of structure. Use chicken wire reinforcement. Chicken wire reinforcement can strengthen the walls by wrapping. Chicken wire can also be used to strengthen practical columns as well as ring beams. And to improve the connection between practical column structural elements with ring beams and wall to column anchoring. Result is to be help the residents of Koto Marapak Village in Padang Pariaman to provide counseling and training to strengthen their homes so that they are earthquake resistant with economical costs. Because this area is very earthquake-prone. The method applied by conducting counseling, field surveys as well as discussions with community leaders, pilot / training (which is guided by the discovery team) that together with the community members work together to provide reinforcement of houses that are earthquake resistant.